ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN UMUM PERDANA DI BEI PERIODE 2015-2017 - Himawan Budi Kuncoro; Rossje Vitarimetawatty Suryaputri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
This study aims to analyze the effect of debt to equity ratio, underwriter reputation, company age, type of industry, return on equity, company size, inflation rate on underpricing of shares in the initial public offering on the IDX. The data used is secondary data obtained from the financial statements of companies listed on the IDX. Determination of the sample in this study using purposive sampling technique with 3 years observation that is 2015-2017 in order to obtain a sample of 59 observing companies. The analysis technique used in this study is multiple linear regression. The analytical tool used to test the hypothesis is SPSS 22. The results of the analysis show that the variabel underwriter reputation, return on equity, and company size negatively affect underpricing, while the debt to equitry ratio, company age, industry type and inflation rate have no effect on underpricing